2013
DOI: 10.1111/are.12175
|View full text |Cite
|
Sign up to set email alerts
|

Comparative growth and mortality of cultured Lion's Paw scallops (Nodipecten subnodosus) from Gulf of California and Pacific populations and their reciprocal transplants

Abstract: This study focused on the comparison of growth and mortality of Lion's Paw scallops Nodipecten subnodosus from Gulf of California and Pacific populations and their reciprocal transplants, cultured in suspended module and bottom culture in Baja California Sur, Mexico. Environmental parameters were monitored to determine site‐specific differences and were correlated with scallops' population‐specific responses. Significant differences in growth were found between sites, populations and grow‐out methods. Growth p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The peninsula forms a geographical barrier for the gene flow between the two scallop stocks, and as a result, a clear genetic separation exists (Petersen et al, 2010). Koch et al (2015) made a study focused on comparing the growth and mortality of lion's paw scallops from the Gulf of California and Pacific populations and their reciprocal transplants, cultured in suspended Nestier trays and bottom structures in Baja California Sur, Mexico. They found that Gulf scallops resisted high diurnal temperature changes at the Pacific site (San Buto) significantly better than Pacific scallops.…”
Section: Introductionmentioning
confidence: 99%
“…The peninsula forms a geographical barrier for the gene flow between the two scallop stocks, and as a result, a clear genetic separation exists (Petersen et al, 2010). Koch et al (2015) made a study focused on comparing the growth and mortality of lion's paw scallops from the Gulf of California and Pacific populations and their reciprocal transplants, cultured in suspended Nestier trays and bottom structures in Baja California Sur, Mexico. They found that Gulf scallops resisted high diurnal temperature changes at the Pacific site (San Buto) significantly better than Pacific scallops.…”
Section: Introductionmentioning
confidence: 99%
“…Von Bertalanffy identified also species, where mass growth would be better described by an exponent a = 0. Moreover, an exponent a L = 0 is widely used to describe the length growth of fish and many authors reported an excellent fit also for e.g., shellfish ( Koch et al, 2015 ). For instance, the FishBase database ( Froese & Pauly, 2017 ) presumes this model and lists growth parameters for 2,320 species.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an exponent aL = 0 is widely used to describe the length growth of fish and many authors reported an excellent fit also for e.g. shellfish (Koch et al, 2015). For instance, the FishBase database (Frose and Pauly, 2017) presumes this model and lists growth parameters for 2320 species.…”
Section: Introductionmentioning
confidence: 99%